Wives tearfully receive husbands degrees, father receives sons diploma - Sakinah, Abdullah; Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 8 November 2022 - A emotional atmosphere enveloped the hall as names were read out as family members took to the stage representing graduands in the sixth session of the 17th Universiti Malaysia Pahang (UMP) Convocation Ceremony.